An in vitro study on the efficacy of nanoparticles and nanocomposites as coating materials on surgical sutures - Heba R. Shebl; Rehab A. Soliman; Omnia M. Abdallah (Scientific Reports)
Abstract Upgrading the surgical sutures, as the main wound closure device, is essential. The evolution of bacterial resistance and the plummeting of antibiotics have directed research toward augmented sutures. Nanotechnology has provided answers to these concerns. The use of bacterial isolates as bio-factory for synthesized silver nanoparticles (AgNPs) and silver nanocomposites via a one pot ex situ method provides environmentally friendly silver nanocomposites in addition to the use of chitosan and polyvinyl alcohol polymers as carriers. Transmission electron microscopy (TEM) and zeta potential analysis revealed spherical negatively charged AgNPs. These nanoparticles and nanocomposites were used as coatings for absorbable vicryl and nonabsorbable silk surgical sutures. Atomic force microscopy (AFM) 3D images of these coated sutures showed a significant decrease in surface roughness with improved surface topography, specifically with chitosan-silver (CS-Ag) vicryl coated sutures with effective attachment of the nanocomposite and nanoparticles thin film on the suture surface. Field emission scanning electron microscopy with energy dispersive x-ray spectroscopy (FE-SEM/EDX) analysis showed the significant presence of the thin film of coating materials on the surface of the sutures and the significant elemental presentation of Ag. Vicryl and silk coated CS-Ag sutures showed significant antibacterial and antibiofilm activities against both gram positive and gram-negative bacterial isolates. AgNPs coated silk and vicryl sutures recorded the lowest amounts of Ag ions at 0.03–0.45 ppm released after 14 days, while polyvinyl alcohol-silver (PVA-Ag) coated ones showed the highest rates at 0.75–0.93 ppm.